Nude and Modified Electrospun Nanofibers, Application to Air Purification - Patricio J. Espinoza-Montero; Marjorie Montero-Jiménez; Stalin Rojas-Quishpe; Christian David Alcívar León; Jorge Heredia-Moya; Alfredo Rosero-Chanalata; Carlos Orbea-Hinojosa; José Luis Piñeiros (Nanomaterials, 2023)
Air transports several pollutants, including particulate matter (PM), which can produce cardiovascular and respiratory diseases. Thus, it is a challenge to control pollutant emissions before releasing them to the environment. Until now, filtration has been the most efficient processes for removing PM. Therefore, the electrospinning procedure has been applied to obtain membranes with a high filtration efficiency and low pressure drop. This review addressed the synthesis of polymers that are used for fabricating high-performance membranes by electrospinning to remove air pollutants. Then, the most influential parameters to produce electrospun membranes are indicated. The main results show that electrospun membranes are an excellent alternative to having air filters due to the versatility of the process, the capacity for controlling the fiber diameter, porosity, high filtration efficiency and low-pressure drop.